Lysozyme in the tears of newborn babies. - Etches, P C (1979)
Tear lysozyme concentration was measured in term, preterm, and small-for-dates infants using a modification of the lysoplate technique. The lysozyme concentration was greater in the term infant than in preterm and small-for-dates infants. The values were found to increase with birthweight and gestation to a term value which is similar to that described in adults. There was no relationship between the lysozyme concentration and the rate of tear production.